2021
DOI: 10.1186/s12876-021-01688-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of meat consumption with NAFLD risk and liver-related biochemical indexes in older Chinese: a cross-sectional study

Abstract: Background Non-alcohol fatty liver disease (NAFLD) is the most common liver disease and an unhealthy lifestyle can lead to an increased risk of NAFLD. The present study aims to evaluate the association of meat consumption with NAFLD risk and liver-related biochemical indexes in middle-aged and elderly Chinese. Methods A cross-sectional study was conducted in individuals who were 45 years or older and underwent a physical examination from April 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…To our knowledge, there are only three observational studies, which had reported similar results. Peng et al [ 23 ], in a cross-sectional study of Chinese participants over the age of 45, examined the association between meat consumption and odds of NAFLD and they found a positive association. Also, in this study, red meat consumption was correlated with serum levels of liver enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, there are only three observational studies, which had reported similar results. Peng et al [ 23 ], in a cross-sectional study of Chinese participants over the age of 45, examined the association between meat consumption and odds of NAFLD and they found a positive association. Also, in this study, red meat consumption was correlated with serum levels of liver enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a large cohort study of 50,045 Iranian participants in the age range of 40 to 75 years had similar results to our results [ 24 ]. Average intake of red/processed meats were higher in studies that performed in non-Iranian population [ 22 23 ]. It is recommended to limit the consumption of red meat to less than 100 g/day for cardio-metabolic health [ 28 ], and the average consumption of red meat in our study and another study conducted in Iran [ 24 ] is less than the recommended values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have confirmed a positive association between red meat consumption and higher serum TG levels. 44 , 45 Red meat is rich in saturated fatty acids and cholesterol. High-fat products and meat can enhance oxidative stress and inflammation, which can lead to excess lipoproteins in the liver and intestines, thus causing hypertriglyceridemia.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] A minimal amount of red and processed meat intake is another characteristic of the MD: meat contains saturated fatty acids (SFAs) and cholesterol which are relevant in NAFLD pathogenesis as demonstrated by some case-control and cross-sectional studies. [23][24][25] Lastly, the typical Mediterranean dietary pattern also involves coffee consumption, which has been shown to be a protective agent for the development and progression of NAFLD. 26,27 Notably, Molloy et al 28 showed that coffee consumption was significantly associated with a reduced prevalence of steatosis and a lower severity NASH: comparing patients with bland steatosis/not-NASH to those with NASH stage 0-1 and also patients with NASH stage 0-1 to those with NASH stage 2-4, there was a significant difference in coffee consumption between the two groups (P = .005 and P = .016, respectively).…”
Section: Its Variantsmentioning
confidence: 99%